The role of the dietitian within family therapy for anorexia nervosa (FT-AN): a reflexive thematic analysis of child and adolescent eating disorder clinician perspectives - Brennan, Cliona; Baudinet, Julian; Simic, Mima; Eisler, Ivan (MDPI AG, 2024)
Background: Despite dietitians being important members of the multidisciplinary team delivering family therapy for anorexia nervosa (FT-AN), their specific responsibilities and roles are unclear and their involvement in the treatment can be a contentious issue. Methodology: Clinicians (n = 20) experienced in the delivery of FT-AN who were working at a specialist child and adolescent eating disorder service responded to an online survey about their experience of including a dietitian in FT-AN and how they understand the role. Both categorical and open-ended questions were used. Reflexive thematic analysis was used to analyse the qualitative free-text responses of clinician perspectives on the role of the dietitian in FT-AN. Results: All clinicians agreed that dietetics had a role within FT-AN and most frequently sought dietetic involvement in the early phases of FT-AN. Reflexive thematic analysis of responses identified three main themes. These were (1) collaboration is key, (2) confidence as a core consideration and (3) case-by-case approach. These themes evidenced the role of the dietitian within FT-AN and highlighted both the benefits and concerns of this involvement. Conclusions: This study demonstrated that dietitians can take a core role as collaborators within therapy-led teams that facilitate joint working and sharing of expertise. However, dietetic input should be considered on a case-by-case basis, given its potential for creating an over-focus on nutrition and potentially diminishing parental confidence in feeding. When indicated for selected cases, nutritional counselling should be offered in joint sessions with the therapist rather than separately. The findings of the study were limited by the small sample size of participants recruited from a single centre and heterogeneity in the professional background of respondents. Although the integration of dietetics within the multidisciplinary team and the ability of dietitians to individualise patient care can enhance FT-AN treatment, potential benefits and disbenefits should be considered for each case.